Microplastics in the crustaceans Nephrops norvegicus and Aristeus antennatus: Flagship species for deep-sea environments?. (December 2019) - Cau, Alessandro; Avio, Carlo Giacomo; Dessì, Claudia; Follesa, Maria Cristina; Moccia, Davide; Regoli, Francesco; Pusceddu, Antonio
Abstract: Ingestion of microplastics (MPs) has been documented in several marine organisms, but their occurrence in deep-sea species remains almost unknown. In this study, MPs were investigated in two economically and ecologically key crustaceans of the Mediterranean Sea, the Norwegian lobster Nephrops norvegicus and the shrimp Aristeus antennatus. Both the species were collected from 14 sites around Sardinia Island, at depths comprised between 270 and 660 m. A total of 89 and 63 stomachs were analysed for N. norvegicus and A. antennatus respectively, and more than 2000 MPs-like particles were extracted and sorted for identification and characterization by μFT-IR. In N. norvegicus, 83% of the specimens contained MPs, with an average abundance of 5.5 ± 0.8 MPs individual −1, while A. antennatus showed a lower frequency of ingestion (67%) and a lower mean number of MPs (1.66 ± 0.1 MPs individual −1 ). Composition and size of particles differed significantly between the two species. The non-selective feeding strategy of N. norvegicus could explain the 3–5 folds higher numbers of MPs in its stomach, which were mostly composed of films and fragments derived by polyethylene and polypropylene single-use plastic items. Contrarily, most MPs in the stomachs of A. antennatus were polyester filaments. The MPs abundance observed in N. norvegicus is among the highest detected in Mediterranean species considering both fish and invertebrates species, and provides novel insights on MPs bioavailability in deep-sea habitats. The overall results suggest that both N. norvegicus and A. antennatus, easily available in common fishery markets, could be valuable bioindicators and flagship species for plastic contamination in the deep-sea. Graphical abstract: Image 1 Highlights: Microplastics (MPs) ingestion was investigated in two deep-sea crustaceans. MPs were present in all investigated sites and in 60–85% of the specimens. MPs ingestion is modulated by the feeding behaviour. Both species can be proxies of MPs in the deep-sea. Abstract : Two deep sea crustaceans of high economic and ecological relevance showed among the highest MPs ingestion ever reported so far and are thus proposed as flagship species for plastic pollution in the deep sea.